2017
DOI: 10.1080/14767058.2017.1361925
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of necrotizing enterocolitis: a review of literature

Abstract: Necrotizing enterocolitis (NEC) is among the most serious gastrointestinal emergency in very low birth weight (VLBW), extremely low birth weight (ELBW) and extremely low gestational age neonates (ELGAN), affecting 7-14% of these neonates. Despite extensive research, the underlying aetiology of NEC still remains blurred. Due to high mortality, morbidity and its delayed presentation, early detection of NEC is considered to be lifesaving. A number of biomarkers have been studied for early detection and prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 121 publications
0
22
0
1
Order By: Relevance
“…Recently, there have been many publications examining NEC biomarkers in the past decades, such as cytokines (IL-8, TGF-β, IL-1RA, IL-1β), calprotectin, the non-protein amino acid citrulline, urine intestinal fatty acid-binding protein (IFABP), serum amyloid A (SAA), fecal calprotectin, the EpCAM/MMp7 ratio, a serum protein panel, volatile organic compounds, acylcarnitines, fibrinogen-g dimers, and so on (Rusconi et al, 2017;Hackam et al, 2018). However, no biomarkers have achieved widespread clinical application, and existing biomarkers cannot reflect intestinal flora disorder (Anatoly et al, 2013;Neu, 2014;Garg et al, 2018); furthermore, such examinations are usually invasive or radioactive (Stoll et al, 2015;Rusconi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been many publications examining NEC biomarkers in the past decades, such as cytokines (IL-8, TGF-β, IL-1RA, IL-1β), calprotectin, the non-protein amino acid citrulline, urine intestinal fatty acid-binding protein (IFABP), serum amyloid A (SAA), fecal calprotectin, the EpCAM/MMp7 ratio, a serum protein panel, volatile organic compounds, acylcarnitines, fibrinogen-g dimers, and so on (Rusconi et al, 2017;Hackam et al, 2018). However, no biomarkers have achieved widespread clinical application, and existing biomarkers cannot reflect intestinal flora disorder (Anatoly et al, 2013;Neu, 2014;Garg et al, 2018); furthermore, such examinations are usually invasive or radioactive (Stoll et al, 2015;Rusconi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, NEC symptoms were evident 2 days after the model was established. There are differences in the clinical manifestation of NEC; mild symptoms, including a swollen abdomen and diarrhea, can rapidly develop into necrosis of the intestinal wall, perforation or peritonitis (2,8). Therefore, prevention is particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of NEC varies from case to case any may affect the entire intestine (6,7). Studies have demonstrated that various factors are associated with an increased risk of developing NEC; its pathogenesis has been explored using animal models in an attempt to develop more effective therapeutic strategies (8,9). The latest studies have indicated that inflammatory cascades serve an important role in the pathogenesis of neonatal NEC (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…The decision between surgical treatment and conservative treatment can, therefore, be difficult. Biomarkers have been one of the important topics of NEC research in the last few years , but these studies have not yet given clinicians any new biomarkers that are reliable enough to be included in the everyday clinic . Hopefully, the future will provide more knowledge in this area.…”
Section: Discussionmentioning
confidence: 99%